2012
DOI: 10.3390/molecules171011990
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Metabolism of Verproside in Rats

Abstract: Verproside, a catalpol derivative iridoid glycoside isolated from Pseudolysimachion rotundum var. subintegrum, is a biologically active compound with anti-inflammatory, antinociceptic, antioxidant, and anti-asthmatic properties. Twenty-one metabolites were identified in bile and urine samples obtained after intravenous administration of verproside in rats using liquid chromatography-quadrupole Orbitrap mass spectrometry. Verproside was metabolized by O-methylation, glucuronidation, sulfation, and hydrolysis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…It is believed that compounds with similar structures have similar metabolic rules, and the metabolism in vitro can be used to predict the metabolic pathways in vivo to some extent [26]. Recently, it was reported that WZ's active lignans including SinA, SolA and SolB were the substrates of CYP3A [6], we performed the in vitro study using mice liver microsome, which could highly express drug-metabolizing phase I enzymes [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that compounds with similar structures have similar metabolic rules, and the metabolism in vitro can be used to predict the metabolic pathways in vivo to some extent [26]. Recently, it was reported that WZ's active lignans including SinA, SolA and SolB were the substrates of CYP3A [6], we performed the in vitro study using mice liver microsome, which could highly express drug-metabolizing phase I enzymes [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that verproside is a major biologically active compound of this plant, showing potent anti-inflammatory, antioxidant, and anti-asthmatic activities [33, 34]. However, verproside is predominantly metabolized to picroside II in vivo [35]. These information led us to evaluate the protective effects of picroside II on airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…M01, M02 and M09 were found as the circulating metabolites in rat plasma, which may be associated with its activity. Although the biotransformation on picroside II have been reported in previous studies [23][24], our observations provided insights into the in vivo disposition of picroside II as a total of six metabolites were newly identified (M03-M08). Further studies should focus on the preparation of the newly identified principal metabolites and the evaluation of their hepatoprotective effects and toxicities.…”
Section: Metabolic Profiles Of Picroside II In Ratsmentioning
confidence: 87%